Comparative Safety of PD-1/PD-L1 Inhibitors for Cancer Patients: Systematic Review and Network Meta-Analysis - Huang, Ya-fang; Xie, Wen-jie; Fan, Hai-yu; Du, Juan (Frontiers in Oncology, 2019)
Background: Comprehensive evidence comparing treatment-related adverse events (trAEs) among PD-1/PD-L1 inhibitors is unavailable. Methods: A systematic review and network meta-analysis (NMA) was conducted. Randomized controlled trials in cancer patients treated with PD1/PD-L1 inhibitors or their combinations with chemotherapy/placebo and compared with PD1/PD-L1 inhibitors/chemotherapy/placebo were identified through comprehensive searches of multiple databases. Bayesian NMA was performed using random-effects model. Relative ranking of treatments was assessed with surface under the cumulative ranking (SUCRA) probabilities. Incidences and odds ratios of trAEs and immune-related adverse events (irAEs) of all-grade (Grade 1-5) and high-grade (Grade 3-5) were estimated. Results: Twenty-three RCTs (14204 patients) comparing six different strategies were included. The incidence of trAEs was lowest for PD-L1 inhibitors (all-grade: pooled incidence=60.4%, SUCRA=77.2%; high-grade: 6.4%, 73.8%). PD-L1 inhibitors plus chemotherapy had the highest incidence of all-grade trAEs (88.6%, 10.1%), while PD-1 inhibitors plus chemotherapy had the highest incidence of high-grade trAEs (8.2%, 9.3%). Using PD-1/PD-L1 inhibitors alone were associated with significant reductions on high-grade trAEs, compared with PD-1/PD-L1 inhibitors plus chemotherapy. PD-1 inhibitors had the highest incidence of irAEs (all-grade: 15.1%, 9.5%; high-grade: 3.5%, 16.8%). Compared with PD-L1 inhibitors, PD-1 inhibitors neither increased trAEs nor irAEs significantly. Results from sensitivity analyses were consistent. Conclusions: Current data showed that PD-L1 inhibitors had the best safety on both trAEs and irAEs. Awareness of the comparative safety could promote further appropriate utilization of PD-1/PD-L1 inhibitors in clinical practice.